The Impact of Culture on Language Learning - Uralov Islom Ural o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Language learning is process which may be impacted by culture. Culture may define several points in language learning. Students are expected to be aware of culture or understand it in order to fully grasp the language. The article provides data about the impacts of culture on language learning.